Tutorial plan to support the english speaking skill of an inga student of an initial teacher education program (2007)
This paper reports on a case study consisting of the implementation of a tutorial plan as a way to support the improvement of the speaking skill of an Inga indigenous student who had difficulties learning English as a third language. This study reveals the similarities of the learning process of the student to a traveler’s journey. On the way, the student asks his tutor for direction and support so he can get to the end of his journey on his own. Likewise, it is described and analyzed how the student was helped to improve his oral communication skill in a more natural and meaningful way through tutoring sessions that incorporated principles of autonomous and task-based learning. Key words: Tutoring, oral skills, autonomous learning, task-based learning Este documento reporta un estudio de caso que consistió en la implementación de un plan tutorial basado en la metodología de aprendizaje por tareas, para apoyar el desarrollo de la habilidad oral de un estudiante indígena inga quien presentaba dificultades en aprendizaje del inglés. El estudio revela la similitud del proceso de aprendizaje del estudiante, con el camino de un viajero. En el trayecto el estudiante solicita orientación y apoyo de la tutora para llegar a su destino por sus propios medios. Así también, se describe y analiza la manera como se promovió y apoyó la producción oral de una manera natural y significativa por medio de sesiones tutoriales enmarcadas en el uso del aprendizaje por tareas y el aprendizaje autónomo. Palabras clave: Acción tutorial, la habilidad oral, el aprendizaje autónomo, el aprendizaje por tareas